Analisis Penjadwalan Waktu Proyek Gedung Puskesmas Ngoro Kabupaten Jombang dengan Menggunakan Metode PDM (Precedence Diagram Methode) - Afnan Ashiddiq Virgatara Setyawan; Titin Sundari; Totok Yulianto; Meriana Wahyu Nugroho (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Time Schedule is used as a guide and control tool for work execution time and productivity of workers, work tools on the project. In terms of productivity control, there are several aspects involved in the monitoring system, such as materials, tools, resources, and scheduling of project activities. Scheduling is the arrangement of resources to complete tasks in achieving targets. by involving components of activities, and time, In order to determine the optimal scheduling and budget. in accordance with time and cost limitations, this study uses the PDM (Precedence Diagram Method) method and the Crashing method through alternative scheduling with the addition of overtime of 1 hour, 2 hours, and 3 hours and knowing the acceleration cost. for each alternative. The results of the acceleration alternative with optimal costs are, alternative 1 adding 1 hour of overtime, the total cost decreased by 0.19% to Rp 3,067,337,201, -. This means that alternative 1 saves costs of Rp 5,984,598, - and is estimated to be one day faster to 119 days.